Western Tv Treasures 150 Episodes - Television Classics ([Minneapolis, Minn.] Mill Creek Entertainment, 2009)
Disc 1: Adventures of Champion (10, episodes, 1955) ; Tate (3 episodes, 1960) -- disc 2: Gabby Hayes show (11 episodes, 1950) ; Lash of the West (1 episode, 1953) ; Night rider (1 episode, 1962) -- disc 3: Cowboy G-Men (13 episodes, 1952) -- disc 4: Adventures of Kit Carson (12 episodes, 1951) -- disc 5: Cisco kid (3 episodes, 1950); Judge Roy Bean (4 episodes, 1956); Buffalo Bill Jr. (6 episodes, 1955) -- disc 6: Adventures of Jim Bowie (7episodes, 1956); Dusty's trail (3 episodes, 1973); Range Rider (3 episodes, 1951) -- disc 7: Annie Oakley (13 episodes, 1954) -- disc 8: Annie Oakley (14 episodes, 1954) -- disc 9: US Marshal/Sheriff of Cochise (4 episodes, 1956); Stories of the century (2 episodes, 1954); Tim McCoy show (4 episodes, 1952) -- disc 10: Hudson's Bay (12 episodes, 1959) -- disc 11: Hudson's Bay (6 episodes, 1959); Roy Rogers show (6 episodes, 1951) -- disc 12: Roy Rogers show (11 episodes, 1951); Roy Rogers and Dale Evans show (1 episode, 1962).